Post-acquisition management in transitional economies: Empirical analysis of acquired company in telecommunication industry - Dušan Marković; Ana urović; Slaana Savović (Economic Themes, 2022)
Growing globalization has created a business environment that encourages companies to internationalize through international acquisitions. The growth in the number and value of international acquisitions in the previous period has increased the number of studies that analyze this phenomenon from different standpoints. Research has shown that the success rate of international acquisitions is relatively low. Poor management of post-acquisition changes, which is particularly complex in transition economies, is cited as the main obstacle in creating value after acquisitions. The aim of the paper is to investigate the factors that contribute to the successful management of post-acquisition changes. The research is based on the case study of the acquisition of Montenegro Telekom by Deutsche Telekom. Data is obtained through employee surveys and interviews with expatriates engaged in acquisitions in transition economies. The research shows that successful management of post-acquisition changes requires change of the corporate culture in the short term and active knowledge transfer support from the parent to the target. Changes in corporate culture aim to encourage innovation among employees and willingness to accept a new business model and process. At the same time, knowledge transfer occurs through intensive employee training on the domestic market, abroad and through online courses and hiring expatriate managers. It turns out that these two processes are complementary and must be implemented simultaneously.
Keywords: L22; M14; M16; 330; Post-acquisition management; restructuring; corporate culture; knowledge transfer; expatriates; transitional economies